Report of the Human Rights Committee Volume II Part 2, 108th session (8–26 July 2013) 109th session (14 October–1 November 2013) 110th session (10–28 March 2014) - United Nations (United Nations, 2014)
This is the official Record of the Report of the Human Rights Committee Volume II Part 2, 108th session (8–26 July 2013) 109th session (14 October–1 November 2013) 110th session (10–28 March 2014)